Comparison between MDCT and Grayscale IVUS in a Quantitative Analysis of Coronary Lumen in Segments with or without Atherosclerotic Plaques - Falcão,João L. A. A. (2015)
Background: The diagnostic accuracy of 64-slice MDCT in comparison with IVUS has been poorly described and is mainly restricted to reports analyzing segments with documented atherosclerotic plaques. Objectives: We compared 64-slice multidetector computed tomography (MDCT) with gray scale intravascular ultrasound (IVUS) for the evaluation of coronary lumen dimensions in the context of a comprehensive analysis, including segments with absent or mild disease. Methods: The 64-slice MDCT was performed within 72 h before the IVUS imaging, which was obtained for at least one coronary, regardless of the presence of luminal stenosis at angiography. A total of 21 patients were included, with 70 imaged vessels (total length 114.6 ± 38.3 mm per patient). A coronary plaque was diagnosed in segments with plaque burden > 40%. Results: At patient, vessel, and segment levels, average lumen area, minimal lumen area, and minimal lumen diameter were highly correlated between IVUS and 64-slice MDCT (p < 0.01). However, 64-slice MDCT tended to underestimate the lumen size with a relatively wide dispersion of the differences. The comparison between 64-slice MDCT and IVUS lumen measurements was not substantially affected by the presence or absence of an underlying plaque. In addition, 64-slice MDCT showed good global accuracy for the detection of IVUS parameters associated with flow-limiting lesions. Conclusions: In a comprehensive, multi-territory, and whole-artery analysis, the assessment of coronary lumen by 64-slice MDCT compared with coronary IVUS showed a good overall diagnostic ability, regardless of the presence or absence of underlying atherosclerotic plaques.